A geochemical model for fumaroles of the Mutnovsky volcano, Kamchatka, USSR - Taran Yu.A.; Pilipenko V.P.; Rozhkov A.M.; Vakin E.A. (Journal of Volcanology and Geothermal Research, 1992)
On the basis of the chemical, isotopic and thermodynamic characteristics of fluids sampled between 1964 and 1989 a genetic model description is given for fumaroles of the Mutnovsky volcano. There are three individual groups of fumaroles in the Mutnovsky crater which show stable activity for a long period of time: “the Active Funnel” (temperatures exceed 600°C), the “Upper Field” (up to 320°C) and the “Bottom Field” (from 100 to 150°C). The three principal zones of emission have different gas composition, water isotopic composition, radioactivity and 3He/4He ratios. The abundance of magmatic components in the high-temperature fumaroles of the “Active Funnel” is much higher than those in gases from the other groups. Emission rate of SO2 from the “Active Funnel” is about 200 t/d, which requires complete degassing as a minimum of 1 km3 of magma every 20 years. Fluids of the “Upper Field” contain up to 80% of steam from the Mutnovsky geothermal system. Temperature variations of the “Bottom Field” fumaroles (from 97°C before 1982 to 151°C in 1989) result from changes in hydrological conditions in the crater. Evaporation of high-saline acid brine which is formed in the interior of the volcano is responsible for the composition of the “Bottom Field” gas-steam discharges.